30 Primary Prevention ICD post-STEMI: Impact of Adoption of Nice vs ESC Guidelines. (6th June 2015) - Wood-Gismera, Scarlett; Boles, Sophie; Dastidar, Amardeep Ghosh; Nightingale, Angus; Ismail, Yasmin; Bucciarelli-Ducci, Chiara
Abstract : Background: It has been demonstrated that implantable cardiac defibrillators (ICD) can be effective in the primary prevention of sudden cardiac death in patients with severe left ventricular systolic dysfunction (LVSD). However, studies have been unable to elucidate any benefit from ICD implantation prior to 40 days post-infarct. Therefore, ESC guidelines recommend ICD implantation in patients with a persistent ejection fraction (EF) </=40% on repeat LV assessment taken at least 40 days post-STEMI. The NICE guidelines are more restrictive, recommending ICD implantation in patients with EF </=35% and QRS duration >120 ms. The extent to which these guidelines are followed in clinical practice is unclear. Aims: To evaluate in a primary percutaneous coronary intervention (PPCI) cohort: Whether patients with LVSD are receiving a re-assessment of their EF at least 40 days post-STEMI. The impact of adoption of ESC versus NICE guidelines on ICD implantation rates for primary prevention. Methods: This was a retrospective observational study carried out at a tertiary referral centre in South West England. Data was collected from consecutive patients referred for PPCI with a diagnosis of STEMI (January to December 2013). LVSD was defined as an EF </=40% according to echocardiography or cardiac MRI. ECG changes were preferentially sourced from the date closest to the follow-up LV assessment. Results: 573 patients were included, of which, 74% were male and the median age was 64 years. 214 patients had LVSD on initial assessment and were alive after 40 days. 29% (62/214) of patients were followed up elsewhere (echo data not available) and hence excluded from further analysis. 76% (115/152) had a repeat assessment of their EF; however, only 70% (80/115) of reassessments were carried out at least 40 days after the acute event. Of these, 41% (33/80) had persistent LVSD. Thus, 28% (33/115) patients qualified for an ICD under ESC guidelines. On the contrary, 3% qualified under the NICE guidelines, as 17/80 had an EF </=35% at repeat echo and only 3 of these had a QRS duration > 120 ms. Conclusion: In a UK PPCI population, significantly more patients would be eligible for an ICD based on ESC compared to NICE guidelines (28% vs. 3%). This would have significant cost implications. The requirement for repeat echocardiography and ECG least 40 days after the STEMI emphasises the need for appropriate linking of care between the PPCI centre and those hospitals undertaking subsequent follow-up. This remains a challenge to the NHS but we need to find ways to achieve it!